(untitled) (Forum Penelitian Agro Ekonomi, 2024)
Soybean is one of the strategic commodities required as a source of vegetable protein in Indonesia. Progressing food and feed industries using soybeans as raw material is in line with population growth causing increased soybean demand. However, since the mid-1970s until now domestic soybean production has not been able to meet national demand. This study aims to give a real figure regarding the performance of production and consumption, as well as the future prospects for the achievement of soybean self-sufficiency in Indonesia. This study was conducted through reviewing literatures as well as exploring and examining the relevant data and information from various sources such as BPS and FAO data, as well as related information from some scientific studies published in books, journals, proceedings, and other publications. The results of this literature review supported by statistical data indicated that soybean area and production peaked in 1992, then it declined sharply until 2013. The very sharp decline in harvested area reflects the disincentive for farmers to grow soybean. This condition will weaken national food security. If there is no significant breakthrough in providing incentives for farmers to grow soybeans, the phenomenon of decline in soybean area and production will continue. Along with the increasing demand for soybean, efforts to achieve self-sufficiency become unrealistic, at least until 2025. It implies that launching soybean self-sufficiency in 2017 is unworkable.